2004
DOI: 10.1111/j.1875-595x.2004.tb00002.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiplaque and antigingivitis efficacy of toothpastes containing Triclosan and fluoride

Abstract: Objective: To compare the reduction of plaque and gingivitis from the following three toothpaste formulations containing: 0.3% Triclosan, 1,000ppm fluoride and 0.13% calcium glycerophosphate in a natural calcium carbonate base (a new paste); 0.2% Triclosan and 1,000ppm fluoride in a precipitated calcium carbonate base; 0.3% Triclosan, 1,000ppm fluoride and Gantrez in a silica base. A control group was maintained, which used commercially available toothpastes without the above actives. Methods: A double‐blind, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…With respect to TCS and TCC, scientific evidence points to known benefits from their application in health care settings by health care professionals, and possibly from TCS-containing toothpaste used by individuals diagnosed with gingivitis. 149 Exclusive sale of TCS/TCC-containing soaps in pharmacies and prescription requirements for TCS in toothpaste may aid in effecting the desirable reduction in unsustainable consumption patterns and with it associated adverse effects. This tiered approach worked well for the now restricted hexachlorophene, whose allowable and prudent applications continue to this date, as a preservative at concentrations of up to 0.1% by weight.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to TCS and TCC, scientific evidence points to known benefits from their application in health care settings by health care professionals, and possibly from TCS-containing toothpaste used by individuals diagnosed with gingivitis. 149 Exclusive sale of TCS/TCC-containing soaps in pharmacies and prescription requirements for TCS in toothpaste may aid in effecting the desirable reduction in unsustainable consumption patterns and with it associated adverse effects. This tiered approach worked well for the now restricted hexachlorophene, whose allowable and prudent applications continue to this date, as a preservative at concentrations of up to 0.1% by weight.…”
Section: Introductionmentioning
confidence: 99%
“…In-vivo, Triclosan's clinical efficacy has been enhanced by combining it either with a copolymer of polyvinyl methyl ether (PVM) and maleic acid (MA) (trade name Gantrez‚), marketed as Colgate Total (Colgate-Palmolive) 29,[41][42][43][44][45] or with zinc citrate as an additional compatible antimicrobial agent, marketed under the Mentadent, Aim, Signal and Pepsodent brands (Unilever Oral Care) 12,14,16,20,46,47 . However, Triclosan does deliver effective clinical efficacy on its own 48,49 and recent work has shown that when present in calcium carbonate-based systems as the sole antimicrobial agent, Triclosan does show measurable in-vitro (as discussed below) and in-vivo activity 50 .…”
Section: Role Of Triclosanmentioning
confidence: 99%
“…In Asia, where calcium carbonate is the abrasive of choice in toothpaste formulations, Triclosan is used as the sole antimicrobial agent in a number of dentifrices. 50 .…”
Section: Triclosan In Calcium Carbonate-based Systemsmentioning
confidence: 99%
“…This yielded the fully conjugated G0:4 N-Boc-L-phenylalanine (4) (77.8 mg, 0.052 mmol, 51.5% yield). 1 H NMR indicated approx 75% purity (from integration of Ph CH 2 CH peaks of reacted and unreacted phenylalanine) with separation from the unreacted phenylalanine difficult due to the small difference in molecular weight between the compounds. Partial G3 PAMAM 2-(tert-butyloxycarbonylamino)-3-phenylpropanoate conjugates.…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractMany oral care products incorporate an antibacterial compound to prevent the formation of dental plaque which predisposes teeth to dental caries or periodontal disease [1]. Triclosan (TCN) is a commonly used antiplaque agent in toothpastes [2,3].
…”
mentioning
confidence: 99%